(When and how) does basic research in clinical psychology lead to more effective psychological treatment for mental disorders?. (July 2022) - Ehring, Thomas; Limburg, Karina; Kunze, Anna E.; Wittekind, Charlotte E.; Werner, Gabriela G.; Wolkenstein, Larissa; Guzey, Melike; Cludius, Barbara
Abstract: An important aim of basic research in Clinical Psychology is to improve clinical practice (e.g., by developing novel interventions or improving the efficacy of existing ones) based on an improved understanding of key mechanisms involved in psychopathology. In the first part of this article, we examine how frequently this translation has happened in the past by reviewing all 40 evidence-based psychological interventions recommended in current clinical guidelines for five important (groups of) mental disorders. Results show that only 23% of treatments showed a very strong link between basic research and the development of the intervention, and further 20% showed a strong link. These findings thus suggest that the route from basic research to clinical innovation may not be as strong historically as is commonly assumed. Important challenges for translational research in clinical psychology are reviewed, leading to the introduction of a new framework, and a discussion of possible solutions to overcome these challenges. Suggestions include increased attention to robust and replicable research findings, a stronger focus on experimental psychopathology research to establish causality of psychopathological mechanisms, a more systematic structural integration of basic and applied research in clinical psychology, a stronger emphasis on mechanisms of change and moderators of clinical interventions, increased attention to clinical subgroups, and emphasizing improvements to existing interventions over the development of novel interventions. Highlights: Basic research in Clinical Psychology aims to ultimately improve clinical practice. Our review shows that translation does not happen as often as usually assumed. There are systematic challenges and obstacles for translation in Clinical Psychology. Possible solutions for these challenges can be suggested. We provide a novel framework for translational research in Clinical Psychology.